An insertion in the caprine IRF3 gene affects macrophage response to B. melitensis infection - Rossi, Ursula Amaranta; Maurizio, Estefanía; Caffaro, María Eugenia; Poli, Mario Andres; Rossetti, Carlos Alberto (Universidad Nacional del Centro de la Provincia de Buenos Aires, 2025)
Poster